Using cultural heritage in history teaching: views from teacher training in Portugal and Brazil - Pinto, Helena; Squinelo, Ana Paula (Pulso. Revista de educación, 2017)
This paper presents two research studies in the field of heritage education carried out in Portugal and Brazil, both of them focusing on the use of heritage in history teaching, within a group of experienced history teachers undertaking continuing education and a group of Brazilian trainee teachers. From an essentially qualitative approach, the research projects aimed at understanding these teachers’ perspectives regarding the use of local cultural heritage - tangible and intangible - in teaching activities, and consequently in student learning, in view of their relationship with the process of making sense of the past. Regarding research results, Portuguese teachers’ responses were more connected to approaching sources after the contextualization of the subjects in substantive terms, but some teachers emphasized the intersection of sources and their interpretation in context, within their proposals of activities for the exploration of local heritage. Brazilian trainee teachers also recognized the possibility of understanding historical processes using different heritage sources, by questioning them and constructing historical interpretations of the past.